Cooperative action of SP-A and its trimeric recombinant fragment with polymyxins against Gram-negative respiratory bacteria - Coya, Juan Manuel; Fraile-Ágreda, Víctor; de Tapia, Lidia; García-Fojeda, Belén; Sáenz, Alejandra; Bengoechea, José A.; Kronqvist, Nina; Johansson, Jan; Casals, Cristina (Frontiers in Immunology, 2022)
The exploration of therapies combining antimicrobial lung proteins and conventional antibiotics is important due to the growing problem of multidrug-resistant bacteria. The aim of this study was to investigate whether human SP-A and a recombinant trimeric fragment (rfhSP-A) have cooperative antimicrobial activity with antibiotics against pathogenic Gram-negative bacteria. We found that SP-A bound the cationic peptide polymyxin B (PMB) with an apparent dissociation constant (KD) of 0.32 ± 0.04 µM. SP-A showed synergistic microbicidal activity with polymyxin B and E, but not with other antibiotics, against three SP-A-resistant pathogenic bacteria: Klebsiella pneumoniae, non-typable Haemophilus influenzae (NTHi), and Pseudomonas aeruginosa. SP-A was not able to bind to K. pneumoniae, NTHi, or to mutant strains thereof expressing long-chain lipopolysaccharides (or lipooligosaccharides) and/or polysaccharide capsules. In the presence of PMB, SP-A induced the formation of SP-A/PMB aggregates that enhance PMB-induced bacterial membrane permeabilization. Furthermore, SP-A bound to a molecular derivative of PMB lacking the acyl chain (PMBN) with a KD of 0.26 ± 0.02 µM, forming SP-A/PMBN aggregates. PMBN has no bactericidal activity but can bind to the outer membrane of Gram-negative bacteria. Surprisingly, SP-A and PMBN showed synergistic bactericidal activity against Gram-negative bacteria. Unlike native supratrimeric SP-A, the trimeric rfhSP-A fragment had small but significant direct bactericidal activity against K. pneumoniae, NTHi, and P. aeruginosa. rfhSP-A did not bind to PMB under physiological conditions but acted additively with PMB and other antibiotics against these pathogenic bacteria. In summary, our results significantly improve our understanding of the antimicrobial actions of SP-A and its synergistic action with PMB. A peptide based on SP-A may aid the therapeutic use of PMB, a relatively cytotoxic antibiotic that is currently being reintroduced into clinics due to the global problem of antibiotic resistance.